Left bundle branch area pacing: A promising modality for cardiac resynchronization therapy - Fu, Yuping; Liu, Peng; Jin, Lingyan; Li, Yingqi; Zhang, Yudi; Qin, Xinghua; Zheng, Qiangsun (Frontiers in Cardiovascular Medicine, 2022)
Cardiac resynchronization therapy (CRT) is recognized as the first-line management for patients with heart failure (HF) and conduction disorders. As a conventional mode for delivering CRT, biventricular pacing (BVP) improves cardiac function and reduces HF hospitalizations and mortality, but there are still limitations given the high incidence of a lack of response rates. Alternative pacing methods are needed either for primary or rescue therapy. In recent years, conduction system pacing (CSP) has emerged as a more physiological pacing modality for simultaneous stimulation of the ventricles, including His bundle pacing (HBP) and left bundle branch pacing (LBBP). CSP activates the His-Purkinje system, allowing normal ventricular stimulation. However, HBP is technically challenging with a relatively low success rate, high pacing threshold, and failure to correct distal conduction abnormalities. Therefore, LBBP stands out as a novel ideal physiological pacing modality for CRT. Several non-randomized studies compared the feasibility and safety of LBBP with BVP and concluded that LBBP is superior to BVP for delivering CRT with a narrower QRS and greater improvements in left ventricular ejection fraction (LVEF) and New York Heart Association (NYHA) functional class. Concurrently, some studies showed lower and stable pacing thresholds and greater improvement of B-type natriuretic peptide (BNP) levels, as well as better mechanical synchronization and efficiency. LBBP ensures better ventricular electromechanical resynchronization than BVP. In this review, we discuss current knowledge of LBBP, compare LBBP with BVP, and explore the potential of LBBP to serve as an alternative primary therapy to realize cardiac resynchronization.